ADHD Is Highly Prevalent in Patients Seeking Treatment for Cannabis Use Disorders. Issue 11 (September 2020) - Notzon, Daniel P.; Pavlicova, Martina; Glass, Andrew; Mariani, John J.; Mahony, Amy L.; Brooks, Daniel J.; Levin, Frances R.
Objective: To estimate the prevalence of ADHD and determine an effective screening test for ADHD in a population-seeking treatment for cannabis use disorders.Method: The Conners Adult ADHD Diagnostic Interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition ( DSM-IV ; CAADID) was used to generate sensitivity and specificity data for ADHD screening tests, which were then administered to 99 participants seeking treatment for cannabis use disorders to estimate ADHD prevalence.Results: The prevalence estimated from the Wender Utah Rating Scale (WURS) was 45% (sensitivity = 0.88, sensitivity of 0.75), from the Conners Adult ADHD Rating Scale (CAARS) 34% (sensitivity = 0.80, specificity = 0.91), from the WURS + CAARS 36% (sensitivity = 0.71, specificity = 0.95), and from the Adult ADHD Self-Report Scale (ASRS) 46% (sensitivity = 0.61, specificity = 0.86).Conclusion: The prevalence of ADHD in adults seeking treatment for cannabis use disorders is estimated to be between 34% and 46%. The WURS paired with the CAARS provides excellent sensitivity and specificity for the diagnosis of ADHD in this population.